2015
DOI: 10.1098/rsbl.2015.0336
|View full text |Cite
|
Sign up to set email alerts
|

The fitness consequences of kin-biased dispersal in a cooperatively breeding bird

Abstract: Cooperative alliances among kin may not only lead to indirect fitness benefits for group-living species, but can also provide direct benefits through access to mates or higher social rank. However, the immigrant sex in most species loses any potential benefits of living with kin unless immigrants disperse together or recruit relatives into the group in subsequent years. To look for evidence of small subgroups of related immigrants within social groups (kin substructure), we used microsatellites to assess relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…This detailed analysis, drawing on more than a decade of data from individually marked individuals, is one of several recent field studies demonstrating the extent and impact of kin substructure in cooperative avian societies. Contrary to previous models, these studies find that sexbiased dispersal does not necessarily eliminate kin associations between members of the dispersing sex, since such alliances can persist during dispersal or form after dispersal [14,15,12]. Nor does sex-biased dispersal necessarily eliminate the risk of inbreeding in cooperative societies, since kin recruitment and short-distance movements can lead to unexpectedly high levels of local genetic relatedness [16][17][18].…”
Section: Introductioncontrasting
confidence: 71%
See 3 more Smart Citations
“…This detailed analysis, drawing on more than a decade of data from individually marked individuals, is one of several recent field studies demonstrating the extent and impact of kin substructure in cooperative avian societies. Contrary to previous models, these studies find that sexbiased dispersal does not necessarily eliminate kin associations between members of the dispersing sex, since such alliances can persist during dispersal or form after dispersal [14,15,12]. Nor does sex-biased dispersal necessarily eliminate the risk of inbreeding in cooperative societies, since kin recruitment and short-distance movements can lead to unexpectedly high levels of local genetic relatedness [16][17][18].…”
Section: Introductioncontrasting
confidence: 71%
“…In superb starlings, however, Pollack and Rubenstein [12] found that sister alliances form via a different, less common, route. Some sisters did emigrate together from their natal group, as discussed above, but the majority of sister pairs involved individuals that joined the same social group in different years.…”
Section: Kin Alliances Can Form Across Clutches and Across Yearsmentioning
confidence: 99%
See 2 more Smart Citations
“…Audio files were saved as 16-bit, 44 kHz wav files and were automatically time-stamped upon recording. Focal birds were identified using a spotting scope, and age, breeding status, and the total number of seasons spent breeding were obtained from behavioral observations and long-term census records (Pollack and Rubenstein, 2015;Rubenstein, 2016).…”
Section: Song Datamentioning
confidence: 99%